The effects of lubrication on the static frictional resistance of orthodontic brackets - Al-Mansouri Noor; Palmer Graham; Moles David R.; Jones Steven P. (Sciendo, 2011)
Background: Difficulties are experienced with the collection and storage of freshly harvested human saliva to use as a lubricant for the laboratory testing of the frictional resistance of orthodontic brackets. In order to overcome these difficulties, researchers have suggested the use of saliva substitutes due to their ease of storage and consistency of properties throughout testing. Others have criticized the use of artificial saliva and prefer the dry state. The present study aimed to compare the effects of human saliva and an artificial saliva (Saliva Orthana®) with the dry state for the static frictional resistance testing of orthodontic brackets.